Die Nederduitsch Hervormde Kerk se sendingwerk 1928–1967: Van besinning tot daad - Wyk, D. J. C. van (Hervormde teologiese studies, 1986)
The missionary work of the Nederduitsch Hervormde Kerk van Afrika: 1928–1967 In this article a short review is given of the missionary work of the Nederduitsch Hervormde Kerk van Afrika during the years 1928 to 1967. Simultaneously it focuses on the exceptional work and contribution of Professor PS Dreyer as member and chairman of the Missionary Board of this Church during the years 1954–1967.